Hypertruth and the foundations of disinformation: an aprioristic approach - Miguel Palomo (Cogent Arts & Humanities, 2025)
Disinformation is typically addressed through posteriori solutions that intervene after its emergence. This study proposes an aprioristic approach, aiming to influence the formation of disinformation narratives before they materialize. By examining the mechanisms that render disinformation persuasive to its recipients, this work introduces the concept of ‘hypertruth’ as a theoretical tool to analyze and understand the ideological and epistemological scaffolding enabling disinformation’s impact. This investigation seeks to contribute to proactive strategies in combating disinformation in digital societies.